Reactivation of Hepatitis B e Antigen-Negative Chronic Hepatitis B in a Bone Marrow Transplant Recipient following Lamivudine Withdrawal. (1st September 2001) - Myers, Robert P; Swain, Mark G; Urbanski, Stefan J; Lee, Samuel S
Abstract : Reactivation of hepatitis B virus (HBV) is a recognized complication of bone marrow transplantation (BMT). Lamivudine is a nucleoside analogue with potent antiviral activity that has been used in the prophylaxis of HBV reactivation in at-risk BMT recipients. Currently, no data exist regarding the safety of nucleoside analogue withdrawal in these patients. A 32-year-old BMT recipient with hepatitis B e antigen (HBeAg)-negative, chronic HBV who developed a serious flare of hepatic inflammation due to a rebound in viral replication within 12 weeks of discontinuing lamivudine therapy is described. The patient remained HBeAg-negative despite high level viremia, suggesting the emergence of a mutant viral strain. The patient's acute hepatitis resolved promptly with the reinstitution of lamivudine therapy. Further studies are necessary to define the safety and efficacy of nucleoside analogues in the prevention of HBV reactivation in at-risk BMT recipients. Clinicians should consider the risk of inducing serious flares of hepatic inflammation due to abrupt nucleoside analogue withdrawal in these patients.